2022
DOI: 10.1109/tsp.2022.3185844
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Joint Active User Detection and Channel Estimation for Massive Connectivity

Abstract: This paper considers joint active user detection (AUD) and channel estimation (CE) for massive connectivity scenarios with sporadic traffic. The state-of-art method under a Bayesian framework to perform joint AUD and CE in such scenarios is approximate message passing (AMP). However, the existing theoretical analysis of AMP-based joint AUD and CE can only be performed with a given fixed point of the AMP state evolution function, lacking the analysis of AMP phase transition and Bayes-optimality. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(121 reference statements)
1
5
0
Order By: Relevance
“…It can also be observed that EM-SBL and AMP generally have equal performance in low average SNR regimes and also outperform OMP and ℓ 2,1 -ADMM due to the fact that they exploit more information from the measurements. In spite of that, it can be observed that AMP is more sensitive to the system configuration, which is consistent with the discussions pointed out by the authors in [38].…”
Section: Performance Of the Mtdssupporting
confidence: 92%
See 1 more Smart Citation
“…It can also be observed that EM-SBL and AMP generally have equal performance in low average SNR regimes and also outperform OMP and ℓ 2,1 -ADMM due to the fact that they exploit more information from the measurements. In spite of that, it can be observed that AMP is more sensitive to the system configuration, which is consistent with the discussions pointed out by the authors in [38].…”
Section: Performance Of the Mtdssupporting
confidence: 92%
“…Based on this property, message passing (MP) algorithms on graphical models have been extensively used to handle the sporadic traffic from MTDs, e.g., using belief propagation (BP) [34], approximate MP (AMP) [21], [35]- [38], and expectation propagation (EP) [20].…”
Section: A Related Literaturementioning
confidence: 99%
“…. , a (l,t) K T is a sparse vector and a (l,t) 0 ≪ K [23], [24]. To characterize the time-variation of the active device indicator a (l,t) , we consider a probabilistic model to characterize the time-variation of the active MTD indicator, where MTDs are supposed to form independent Markov chains by a couple of transition probabilities p (01) {a…”
Section: System Model a System Modelmentioning
confidence: 99%
“…For both formulations, we derived computationally-efficient algorithms based on the alternating direction method of multipliers (ADMM). Furthermore, several theoretical analysis studies have investigated the performance of AMP for JUICE in correlated MIMO channels, in terms of activity detection accuracy [20], [21], channel estimation [21] and achievable rate [15].…”
Section: A Related Workmentioning
confidence: 99%
“…While the works in [14]- [21] address the JUICE problem under the more practical spatially correlated MIMO channels, they make the assumption that the channel distribution information (CDI) for all the UEs are fully known to the BS at any transmission instance. However, this assumption can be challenging to fulfill in realistic scenarios, as the BS cannot track the CDI of the UEs with long inactive status.…”
Section: A Related Workmentioning
confidence: 99%